Bridging the Theory-Practice Gap in Counselor Education: The Impact of OBE-PBL Integrated Modules on Community Counseling Competence and Cognitive Load - Rofiqa Duri; Eko Sujadi; syaiful indra (Tarbawi : Jurnal Ilmu Pendidikan, 2026)
The persistent theory-practice gap between theoretical mastery and clinical proficiency in counselor education is a global challenge that demands outcome-driven pedagogical interventions. This study aims to design, validate, and evaluate the efficacy of a Community Counseling Practicum Module that synthesizes the Outcome-Based Education (OBE) framework and the Problem-Based Learning (PBL) method among pre-service counselors in Indonesia. Employing a Research and Development (R&D) approach integrated with a pre-experimental design (One-Group Pretest-Posttest), the module was evaluated by an expert panel (N = 5) and field-tested on a cohort of students (N = 30). Feasibility analysis utilizing the Content Validity Index (CVI) demonstrated a near-perfect degree of constructive alignment (S-CVI = 0.98). Efficacy testing revealed a highly significant improvement in clinical and analytical competencies (p < 0.001), with a large effect size (Cohen’s d = 1.50). Nevertheless, the acceleration rate of individual comprehension remained within the moderate spectrum (N-Gain = 0.45). This finding illustrates the high cognitive load induced by real-world crisis resolution simulations, which imperatively necessitates persistent scaffolding from educators. Theoretically, this study validates the compatibility of the OBE framework with the behavioral sciences and simultaneously offers an empirical blueprint for transforming pre-service students into empathetic problem solvers. Further investigations utilizing Randomized Controlled Trials (RCTs) are recommended to substantiate the generalizability of these findings in future contexts